Characterization of novel phages KPAФ1, KP149Ф1, and KP149Ф2 for lytic efficiency against clinical MDR Klebsiella pneumoniae infections - Dandekar, Shraddha S.; Thanikkal, Sinta; Londhe, Arti; Bhutada, Pankhudi; Saha, Ujjayni; Pawar, Shubhankar; Samson, Rachel; Dharne, Mahesh; Saroj, Sunil D.; Koratkar, Santosh (Microbial Pathogenesis, 2025)
Phage therapy offers a promising approach to the increasing antimicrobial resistance of Klebsiella pneumoniae. This study highlights three novel lytic bacteriophages-KPAc1, KP149c1, and KP149c2-targeting multidrugresistant (MDR) K. pneumoniae. These phages belong to the Myoviridae and Podoviridae family and demonstrate their efficacy and stability across a wide range of temperatures (up to 60 degrees C) and pH levels (pH 4 to 11). Genomic analysis reveals that they are free from virulence, toxicity, and antimicrobial resistance genes, making them promising candidates for therapeutic use. Among these phages, KPAc1 showed the highest lytic activity with a 26.15% lysis against MDR K. pneumoniae isolates. Additionally, a phage cocktail comprising all three phages improved lytic efficacy to 32.30%. This study also examined the antimicrobial resistance profiles of K. pneumoniae isolates, emphasizing the critical need for alternative treatments. By effectively targeting resistant strains, these phages offer a potential candidacy to be used as a viable alternative or a complementary antimicrobial agent to traditional antibiotics, opening up the possibility for advanced phage-based therapies. The promising results from this study pave the way for developing new treatments that could significantly improve patient care and outcomes from the growing issue of resistant bacterial infections.
Keywords: Antimicrobial resistance; Bacteriophage; MDR-Klebsiella pneumoniae; Phage cocktail; Phage therapy